2011
DOI: 10.1021/la203125x
|View full text |Cite
|
Sign up to set email alerts
|

Tuning High Aqueous Phase Uptake in Nonionic Water-in-Oil Microemulsions for the Synthesis of Mn–Zn Ferrite Nanoparticles: Phase Behavior, Characterization, and Nanoparticle Synthesis

Abstract: In this work, the formation of water-in-oil (w/o) microemulsions with high aqueous phase uptake in a nonionic surfactant system is investigated as potential media for the synthesis of Mn-Zn ferrite nanoparticles. A comprehensive study based on the phase behavior of systems containing precursor salts, on one hand, and precipitating agent, on the other hand, was carried out to identify key regions on (a) pseudoternary phase diagrams at constant temperature (50 °C), and (b) pseudobinary phase diagrams at constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Recently, Stubenrauch et al (Magno et al, 2009) and Sanchez-Dominguez et al (Aubery et al, 2011) have reported systematic studies on the effects of addition of reactants to nonionic microemulsion systems. It was shown (Magno et al, 2009) that, depending on the aqueous nature of nonionic microemulsion systems, and the salting-in or salting-out effect of the additives, both increase or decrease on the water solubilization could be obtained.…”
Section: Effect Of Precursor Salts and Additives On The Phase Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Stubenrauch et al (Magno et al, 2009) and Sanchez-Dominguez et al (Aubery et al, 2011) have reported systematic studies on the effects of addition of reactants to nonionic microemulsion systems. It was shown (Magno et al, 2009) that, depending on the aqueous nature of nonionic microemulsion systems, and the salting-in or salting-out effect of the additives, both increase or decrease on the water solubilization could be obtained.…”
Section: Effect Of Precursor Salts and Additives On The Phase Behaviormentioning
confidence: 99%
“…In the studies by our group on the effects of addition of precursor salts and precipitating agent to the non-ionic microemulsion system aqueous solution / Synperonic® 13/6.5 / isooctane (Aubery et al, 2011), several factors were taken into account: phase behavior (pseudoternary phase diagrams at constant temperature), dynamicity (presence or absence of percolation in W/O structures, or formation of bicontinuous microemulsions), and droplet size (DLS). It was possible to obtain w/o microemulsions at a wide range of overlapping compositions for both precursor salts and precipitating agent.…”
Section: Effect Of Precursor Salts and Additives On The Phase Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics have enabled the use of nanosized magnetic materials in biomedicine (e.g., as bioseparators), drug delivery systems, medical diagnostics, and cancer thermotherapy [5][6][7]. Due to the new applications of ferrites ways of synthesizing them, other than the ceramic method, such as the sol-gel [8,9], the precipitation [10,11], the mechanochemical [12,13], the hydrothermal [14,15], the combustion [16][17][18][19][20], and the microemulsion methods [21,22], are being widely investigated. The unquestionable advantages of the above methods are: the mixing together of the reagents at the molecular level, energy efficiency, the fact that only one process stage is required, and the absence of secondary pollution or material loss.…”
Section: Introductionmentioning
confidence: 99%
“…These very different processes are associated to a great range of catalytic materials. The microemulsion method, based on water-in-oil, oil-in-water and bicontinuous ME, has shown to be suitable for the preparation of all these different types of materials [12][13][14][15][16][17][18][19][20][21][22].Even though a few valuable efforts were previously done to understand the formation of nanomaterials in ME systems [23][24][25], comprehensive research in this area is still needed to clarify this process, in order to reach a better control of nanoparticle characteristics and to understand why the formed nanoparticles present specific catalytic properties compared to the materials with the same composition but prepared by traditional methods. Especially advanced analytical tools for deep…”
mentioning
confidence: 99%